Intestinal Levodopa/Carbidopa Infusion as a Therapeutic Option for Unresponsive Freezing of Gait after Deep Brain Stimulation in Parkinson's Disease. (14th May 2020) - González-Herrero, Belén; Jauma-Classen, Serge; Gómez-Llopico, Roser; Plans, Gerard; Calopa, Matilde
Abstract : Background . Treatment of freezing of gait (FOG) is always challenging because of its unpredictable nature and multifactorial physiopathology. Intestinal levodopa infusion has been proposed in recent years as a valuable option for its improvement. FOG in Parkinson's disease (PD) can appear after deep brain stimulation in patients who never had gait symptoms. Objective . To study the effects of intestinal levodopa/carbidopa infusion in unresponsive-FOG that appears in PD patients treated with subthalamic nucleus deep brain stimulation. Methods . We retrospectively collected and analyzed demographic, clinical, and therapeutic data from five PD patients treated with subthalamic nucleus stimulation who developed unresponsive-FOG and received intestinal levodopa/carbidopa infusion as an alternative therapy. FOG was measured based on scores in item 14 of the Unified Parkinson's Disease Rating Scale before and after intestinal levodopa infusion. Results . Administration of intestinal levodopa caused improvement of FOG in the "ON" state in four patients (80%) by 2 or more points in item 14 of the Unified Parkinson's Disease Rating Scale. The improvement was maintained for at least 12 months. Conclusions . Intestinal levodopa infusion may be a valuable therapeutic option for unresponsive-FOG developed after subthalamic nucleus deep brain stimulation.